Instagram influencer marketing: Perceived social media marketing activities and online impulse buying - Koay, Kian Yeik *; Teoh, C. W.; Soh, Patrick C. H. (University of Illinois at Chicago University Library, 2021)
The main objective of this research is to investigate the impact of social media marketing activities — restricted onlyto Instagram influencers — on online impulse buying through the mediating effect of source credibility (attractiveness,expertise, and trustworthiness), predicated on Stimulus-Organism-Response (S-O-R) theory. The hypothesisedrelationships were examined using cross-sectional data obtained from 273 Instagram users. Partial least squaresstructural equation modelling (PLS-SEM) using the SMART-PLS software was employed as the primary data analysismethod. The results revealed that the perceived social media marketing activities of Instagram influencers have asignificant positive influence on the perceptions of followers pertaining to all three dimensions of source credibility(attractiveness, expertise, and trustworthiness). In turn, only attractiveness and trustworthiness were found to have asignificant positive influence on online impulse buying. Moreover, this study revealed that it was the perceivedattractiveness and trustworthiness of Instagram influencers that were the influential mediating factors in therelationship between perceived social media marketing activities and online impulse buying. There is a dearth ofstudies that have been conducted on the examination of the mechanism through which Instagram influencers’ socialmedia marketing activities influence online impulse buying. This study is significant as it provides new insights intothe importance of Instagram influencers social media marketing activities in affecting followers’ online impulsebuying through source credibility